Pelaksanaan Tugas-tugas Sekretaris pada Bidang Administrasi dan Fasilitas di PT PLN (PERSERO) Wilayah Aceh - Eva Wahyuni; M Djamil HS (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2021)
-This research investigates the implementation of a secretary's duties in the field of administration and facilities at PT PLN (Persero) Aceh Region. A qualitative approach was used with observation, interview, and documentation study techniques to obtain an in-depth understanding of the role and contribution of secretaries in supporting company operations. The research results revealed that secretaries were responsible for administrative tasks such as schedule management, document processing, and meeting coordination. They are also involved in facilities management, interdepartmental coordination, and information management. The secretary's strategic role in facilitating communication, coordination and information management throughout the organization is highlighted. The findings show that the use of information technology, technology integration, and strong relationships between departments are important aspects in carrying out secretarial duties. The implications of this research include the need to develop multifunctional competencies, integrate technology, and strengthen interdepartmental relationships. With a better understanding of their role, secretaries can become valuable assets in achieving company operational goals and improving the overall performance of the organization.